The Relationship between Personal Hygiene Behavior with Vaginal Discharge in Young Women : Hubungan Perilaku Personal Hygiene dengan Kejadian Keputihan pada Remaja Putri - Amalia Putri, Arizki; Amelia Kusumawardhani, Paramitha; Cholifah, Siti (Universitas Muhammadiyah Sidoarjo, 2021)
Vaginal discharge is a sign of disturbance to the body, can be fisiological and pathological. One of factor is personal hygiene. Vaginal discharge incidence in psychology students at Universitas Muhammadiyah Sidoarjo higher (80%) than in Sidoarjo at 40%. This research is for determining the relationship between personal hygiene behavior with vaginal discharge. Designed used analytical with cross sectional approach. The instrument is questionnaire. Sampels are 23 in simple random sampling from 30 population. The result showed fisiological vaginal discharge more happens to good personal hygiene than not good. Test result P=0,026 < α(0,05), Ho is rejected. Conclusion there is a relationship between personal hygiene behavior with vaginal discharge. Vaginal discharge is a sign of disturbance to the body, can be fisiological and pathological. One of factor is personal hygiene. Vaginal discharge incidence in psychology students at Universitas Muhammadiyah Sidoarjo higher (80%) than in Sidoarjo at 40%. This research is for determining the relationship between personal hygiene behavior with vaginal discharge. Designed used analytical with cross sectional approach. The instrument is questionnaire. Sampels are 23 in simple random sampling from 30 population. The result showed fisiological vaginal discharge more happens to good personal hygiene than not good. Test result P=0,026 < α(0,05), Ho is rejected. Conclusion there is a relationship between personal hygiene behavior with vaginal discharge.